2014
DOI: 10.1007/s10815-014-0254-8
|View full text |Cite
|
Sign up to set email alerts
|

Putative mesenchymal stem cells isolated from adult human ovaries

Abstract: Purpose The purpose of this study was to show that healthy adult human ovaries can be a source of cells showing typical MSCs characteristics under in vitro conditions. Methods and results The cells, which were isolated from ovarian cortex tissue and named putative ovarian mesenchymal stem cells (PO-MSCs), were compared to bone marrowderived MSCs (BM-MSCs) and to adult human dermal fibroblasts (HDFs). The results of a gene expression analysis using the Human Mesenchymal Stem Cell RT² Profiler™ PCR Array reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
4
16
0
Order By: Relevance
“…We carefully followed the minimal qualification criteria suggested by the International Society for Cell Therapy to isolate MSC + cells, ≥95% of population expressing CD73, CD90 and CD105, and ≤2% of the population expressing hematopoietic marker CD45. 36 As expected, sorted MSC + cells were stably expressed above markers after several passages of culturing, retained higher levels of stemness marker OCT3/4 and underwent induced differentiation into mesenchymal lineages, thereby confirming their multi-potentiality compared with MSC − cells.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We carefully followed the minimal qualification criteria suggested by the International Society for Cell Therapy to isolate MSC + cells, ≥95% of population expressing CD73, CD90 and CD105, and ≤2% of the population expressing hematopoietic marker CD45. 36 As expected, sorted MSC + cells were stably expressed above markers after several passages of culturing, retained higher levels of stemness marker OCT3/4 and underwent induced differentiation into mesenchymal lineages, thereby confirming their multi-potentiality compared with MSC − cells.…”
Section: Discussionsupporting
confidence: 74%
“…Expanded ovarian cells (passages 1‐3) were incubated with Fc‐blocking antibody (Miltenyi Biotec, Bergisch Gladbach, Germany) for 15 minutes to prevent unspecific binding. After washing, cells were again incubated with antibody cocktail containing mesenchymal stem/stromal cell markers anti‐human CD90‐FITC, CD73‐APC and CD105‐PE (Abcam, Cambridge, UK) for 30 minutes at 4°C. Stained single suspended cells were washed twice and passed through a MoFlo XDP flow cytometer (Beckman‐Coulter, Brea, CA, USA) to isolate ovarian MSC.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study with human ovarian MSC also demonstrated the ability of those cells to differentiate into mesenchymal, ectodermal and endodermal lineages, concurring with our results describing the high differentiation potential of the cells from the ovary. 7 Canine adipose-derived stem cells have already been shown to differentiate into germ cells, 49 so our next step was to verify if the cells derived in the present paper also possessed the capability to differentiate into putative germ cells by using the culture conditions for female germ cells derived from the ovary of neonatal mice. 15,16 After 2 weeks in this media, the cells changed their morphology from fibroblast-like to colonies of rounded cells that were positive for OCT4 and DDX4 by immunocytochemistry.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, they could also derive from "resident" MSCs located to the tissues where the tumor develops. Indeed, MSCs are not restricted to the bone marrow and are found in virtually all tissues, including ovaries [29]. Another possible origin could be adipose tissue, which is a source of MSCs called adipose tissue-derived stromal cells (ADSC).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can display different phenotypes and functions, depending on the type of tissue from where they are isolated, including, among others, ovary, bone marrow, adipose tissue, heart and bladder [28,29]. Thus our aim was to analyze if CA-MSCs acquired specific functions because of their surrounding tumor cells.…”
Section: Bm-mscs Could Differentiate Into Ca-mscs In a Tumoral Microementioning
confidence: 99%